2007
DOI: 10.1007/s00264-007-0490-y
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration in arthroplasty: can simvastatin promote bone response to implants?

Abstract: Cementless fixation depends on bone ingrowth for long-term success. Simvastatin as a lipid lowering agent has been demonstrated to have osteoanabolic effects. This study was designed to measure the possible effect of simvastatin on implant osseointegration. Bilateral femoral implantation of titanium cylinders was performed in 20 rabbits. Blood lipid levels were measured pre-and postoperatively. Scanning electron microscopy (SEM) was used to measure the percentage of the surface of each implant in contact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 29 publications
0
41
0
7
Order By: Relevance
“…Ten studies presented some data on mechanical tests, including removal torque analysis, push‐out test, pull‐out test and push‐in test, to assess the strength of the newly formed bone around implants. Eight studies showed significant results for the groups with statins compared to the control groups after at least 2 weeks. One publication showed significant results after 56 days.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies presented some data on mechanical tests, including removal torque analysis, push‐out test, pull‐out test and push‐in test, to assess the strength of the newly formed bone around implants. Eight studies showed significant results for the groups with statins compared to the control groups after at least 2 weeks. One publication showed significant results after 56 days.…”
Section: Resultsmentioning
confidence: 99%
“…Statins have therefore been proposed as potential agents in the treatment of osteoporosis. Previous studies also suggest that simvastatin can promote osteogenesis around titanium implants (Ayukawa et al 2004, Ayukawa et al 2010, Basarir et al 2009).…”
Section: Date: Accepted 8 September 2011mentioning
confidence: 85%
“…Previous studies also suggest that simvastatin can promote osteogenesis around titanium implants (Ayukawa et al. , Ayukawa et al , Basarir et al ).…”
mentioning
confidence: 86%
“…In multiple animal studies, systemic administration of simvastatin after implant insertion has been demonstrated to promote osseointegration, increase bone density around implants and crucially, to increase the mechanical strength/stability of the bone-implant interface [25][26][27][28] In addition to systemic statin administration it has been proposed that local application of statins (particularly fluvastatin) to implants may promote similar osteogenic effects, increasing mechanical strength and improving peri-implant bony calcification [30][31][32] .…”
Section: Statins and Osseointegration Of Prosthetic Implants And Bonementioning
confidence: 99%